'The hospital and everyday life are two worlds': Patients' and healthcare professionals' experiences and perspectives on collaboration in the kidney transplantation process. Issue 4 (10th August 2019) - Nielsen, Charlotte; Agerskov, Hanne; Bistrup, Claus; Clemensen, Jane
Abstract: Aim: To explore patients' and healthcare professionals' experiences and perspectives on collaboration in the kidney transplantation process. Design: A qualitative study with a phenomenological‐hermeneutic approach. Method: Participant observation and interviews were conducted with 18 patients, together with a focus group with eight healthcare professionals from April 2016–January 2017. The data analysis was inspired by Ricoeur's theory. Results: While patients acknowledged that the healthcare professionals were experts, they also requested an everyday life approach to treatment and care, because both professional knowledge and everyday life experiences were needed to manage everyday life. A contrast between patients' experiences and healthcare professionals' knowledge was identified, and the empowerment approach could be a way to combine the different perspectives.